Ascesa o declino dell’ADHD? La scienza nella definizione dei problemi sociali - Caniglia, Enrico (SocietàMutamentoPolitica, 2018)
Constructionist theory of social problems has studied the role of scientists as claims-makers engaged in the definition and processing of social problems. Specially, constructionist sociologists focus on the scientific idiom as a resource for claims. However, the employ of scientific idiom does not mean broader consensus about the definition of a social problem, but it brings with it a lot of disagree. The paper deeps the interaction between science and claims-making with the analysis of a case from Neurosciences and Psychiatry research: the controversy on ADHD, a childhood mental disturb whose true is very conflicted. The paper shows as claims-making and scientific debate are the same thing, because the science is just a form of powerful rhetoric.